Investigating the Effect of Adding Zirconium Oxide and Titanium Oxide Nanoparticles on the Flexural Strength of Heat Cure Acrylic Resin - Masomeh Rostamzadeh; Kavian Rostami; Farshad Rahimi (Mashhad University of Medical Sciences, 2024)
Background: Adding nanoparticles as filler aims to improve the mechanical properties of acrylic resin and reduce the incidence of fracture in them. This study aimed to investigate the effect of adding zirconium oxide and titanium oxide nanoparticles to acrylic resin on its flexural strength.Methods and Materials: In this in-vitro study, surface modification of ZrO2 and TiO2 nanoparticles have been done by combining with silane coupling agent (trimethoxysilylpropyl methacrylate), and 25 samples of acrylic resin with 2.5*10*65 mm dimensions have been made. 5 groups were divided into control, 1 and 5% TiO2, 1 and 5% ZrO2. Flexural strength was evaluated by universal testing machine. Data were analyzed by One-Way ANOVA and Tukey's post hoc test. P < 0.05 was considered as statistically significant.Results: A significant increase in the flexural strength of acrylic resin modified with 1% zirconium oxide compared to the control sample was observed, with an average difference of 22.082 MPa (p<0.001). The difference in bending strength was significant between the control group and the groups containing nanoparticles (p<0.05). The highest and lowest bending strengths were found in the groups with 1% zirconium oxide, averaging 98.53±2.77 MPa, and 5% titanium oxide, averaging 61±1.52 MPa, respectively. There was a significant difference in flexural strength between the 1% and 5% zirconium oxide groups, with an average of 15.98 MPa (p<0.001). Additionally, there was no significant difference in flexural strength between the 1% and 5% titanium oxide groups, with an average of 4.16 MPa (p=0.06).Conclusion: Based on the findings, ZrO2 nanoparticles improve and TiO2 nanoparticles weaken the flexural strength of acrylic resin. Also, by increasing the concentration of nanofiller, the mechanical properties of acrylic resin are weakened.